2019
DOI: 10.1136/bmjopen-2018-025579
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the risk of stroke among patients with type 2 diabetes: a systematic review and meta-analysis of C-statistics

Abstract: ObjectiveStroke is a major cause of disability and death worldwide. People with diabetes are at a twofold to fivefold increased risk for stroke compared with people without diabetes. This study systematically reviews the literature on available stroke prediction models specifically developed or validated in patients with diabetes and assesses their predictive performance through meta-analysis.DesignSystematic review and meta-analysis.Data sourcesA detailed search was performed in MEDLINE, PubMed and EMBASE (fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 88 publications
1
20
0
1
Order By: Relevance
“…While it is widely perceived that the English language is the primary language of science, the choice of scientific results in a particular language can incorporate language bias and may lead to incorrect conclusions [ 39 ]. We were only able to use C-statistics to compare the model performance, which could be insensitive to distinguish a model’s ability to correctly stratify patients into clinically relevant risk groups [ 39 , 40 ]. Calibration was quantified by different measures, and different studies often reported different calibration measures.…”
Section: Discussionmentioning
confidence: 99%
“…While it is widely perceived that the English language is the primary language of science, the choice of scientific results in a particular language can incorporate language bias and may lead to incorrect conclusions [ 39 ]. We were only able to use C-statistics to compare the model performance, which could be insensitive to distinguish a model’s ability to correctly stratify patients into clinically relevant risk groups [ 39 , 40 ]. Calibration was quantified by different measures, and different studies often reported different calibration measures.…”
Section: Discussionmentioning
confidence: 99%
“…Among models predicting absolute risk of macrovascular complications [28][29][30], the majority originate from study samples located in Europe (the UK Prospective Diabetes Study [UKPDS] risk engines and outcomes models 1&2 [31][32][33][34], Action in Diabetes and Vascular Disease: Preterax and Diamicron MR Controlled Evaluation [ADVANCE] model [35] and two Swedish National Diabetes Register [NDR] models [36,37]) or the USA and/or Canada (e.g. RECODe models [14], the Cardiovascular Health Study [CHS] score [38] and Atherosclerosis Risk in Communities [ARIC] model [39]).…”
Section: Risk Models For the Prediction Of Macrovascular Complicationsmentioning
confidence: 99%
“…Approximately one-third of all stroke patients have diabetes [119]. People with diabetes are at a twofold to fivefold increased risk for stroke compared with people without diabetes [120].…”
Section: Stroke Among Diabetic Patients 25%mentioning
confidence: 99%